Magneto-polar fluid flow through a porous medium of variable permeability in slip flow regime - Gaur, P.K.; Jha, Abhay Kumar; Sharma, Ram Prakash (Zielona Góra: Uniwersytet Zielonogórski)
A theoretical study is carried out to obtain an analytical solution of free convective heat transfer for the flow of a polar fluid through a porous medium with variable permeability bounded by a semi-infinite vertical plate in a slip flow regime. A uniform magnetic field acts perpendicular to the porous surface. The free stream velocity follows an exponentially decreasing small perturbation law. Using the approximate method the expressions for the velocity, microrotation, and temperature are obtained. Further, the results of the skin friction coefficient, the couple stress coefficient and the rate of heat transfer at the wall are presented with various values of fluid properties and flow conditions.
Keywords: polar fluid; MHD; permeability; slip-flow; heat transfer